The Effect Of Nurses' Self-Efficacy And Social Support On Job Burnout In Nurses At Dr. Pirngadi Regional General Hospital Medan City - Muhammad Hidayat; Chrismis Novalinda Ginting; Masryna Siagian (Universitas Pahlawan Tuanku Tambusai, 2025)
Job burnout is a common psychological condition experienced by nurses due to high work pressure, heavy workload, and continuous emotional demands. Two important factors believed to influence job burnout are self-efficacy and social support. This study aims to analyze the influence of self-efficacy and social support on the level of job burnout in nurses. This study used a quantitative method with a cross-sectional approach. A sample of 100 nurses was taken using a purposive sampling technique. The research instrument was a structured questionnaire that measured the level of self-efficacy, social support, and job burnout. Data analysis was performed using univariate, bivariate (Chi-Square test), and multivariate (logistic regression). The results showed that self-efficacy had a significant effect on job burnout (p = 0.019), while social support showed no significant effect (p = 0.397). Most respondents had high self-efficacy (60%) and experienced moderate to high levels of job burnout. Self-efficacy is a protective factor against job burnout in nurses, while social support did not significantly influence this study. Therefore, improving self-efficacy needs to be a focus of interventions to reduce job burnout levels in hospital settings.